Linguistic Features of the Modern Textual Computer-Mediated Communication of Russian-Speaking Youth - Sevostyanova, Irina (Stephanos Peer reviewed multilanguage scientific journal, 2024)
In recent years, young people have been spending more and more time in virtual reality, where their speech acquires various unique features. Textual computer-mediated communication (TCMC) of young people has a wide variety of features that have not been sufficiently studied to date. Due to the lack of information on the characteristics of the TCMC of young people in the Internet space, a sample observation and a linguistic survey were conducted, in which 165 representatives of Russian-speaking youth from 6 subjects of the Russian Federation took part. This study contributed to the disclosure of new previously little-studied aspects. As a result, a number of characteristic features were identified at lexical, spelling and punctuation levels. The findings can be applied to improve the effectiveness of intergenerational communication.